2016
DOI: 10.1159/000446909
|View full text |Cite
|
Sign up to set email alerts
|

Renal Sympathetic Denervation: Hibernation or Resurrection?

Abstract: The most current versions of renal sympathetic denervation have been invented as minimally invasive approaches for the management of drug-resistant hypertension. The anatomy, physiology and pathophysiology of renal sympathetic innervation provide a strong background supporting an important role of the renal nerves in the regulation of blood pressure (BP) and volume. In addition, historical data with surgical sympathectomy and experimental data with surgical renal denervation indicate a beneficial effect on BP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Regarding the latter, a post‐hoc analysis of the study revealed that the majority of patients received 4‐6 ablations per artery, and of major importance only 19 participants received a circumferential ablation of both renal arteries . Of note, blood pressure response was associated with the number of ablations, and patients receiving more than 14 ablations experienced a sufficient systolic blood pressure reduction (office: 14 mm Hg; ambulatory: 7 mm Hg), thus underlining the importance of adequate renal denervation . It is noteworthy that the study by Denegri and colleagues actually duplicates the findings of the post‐hoc analysis of Symplicity‐3, because for a similar number of ablations an identical blood pressure reduction is achieved.…”
mentioning
confidence: 85%
“…Regarding the latter, a post‐hoc analysis of the study revealed that the majority of patients received 4‐6 ablations per artery, and of major importance only 19 participants received a circumferential ablation of both renal arteries . Of note, blood pressure response was associated with the number of ablations, and patients receiving more than 14 ablations experienced a sufficient systolic blood pressure reduction (office: 14 mm Hg; ambulatory: 7 mm Hg), thus underlining the importance of adequate renal denervation . It is noteworthy that the study by Denegri and colleagues actually duplicates the findings of the post‐hoc analysis of Symplicity‐3, because for a similar number of ablations an identical blood pressure reduction is achieved.…”
mentioning
confidence: 85%
“…The results of SYMPLICITY HTN-3 became the focus of extensive debate and provoked efforts to identify and supplement the factors contributing to the failure 1317 . As a result, there was a renewed interest in the renal nerve anatomy and physiology, and a substantial number of studies on the anatomy of the renal artery and peri-renal sympathetic nerve have since been published.…”
Section: Introductionmentioning
confidence: 99%